The Role of NK Cells and Innate Lymphoid Cells in Brain Cancer - Sedgwick, Alexander James; Ghazanfari, Nazanin; Constantinescu, Patrick; Mantamadiotis, Theo; Barrow, Alexander David (Frontiers in Immunology, 2020)
The brain is considered an immune privileged site due to the high selectivity of the blood-brain barrier which restricts the passage of molecules and cells into the brain parenchyma. Recent studies have highlighted active immunosurveillance mechanisms in the brain. Here we review emerging evidence for the contribution of innate lymphoid cells (ILCs) including natural killer (NK) cells to the immunosurveillance of brain cancers focusing on glioblastoma, one of the most aggressive and most common malignant primary brain tumors diagnosed in adults. Moreover, we discuss how the local tissue microenvironment and unique cellular interactions influence ILC functions in the brain and how these interactions might be successfully harnessed for cancer immunotherapy using insights gained from the studies of autoimmunity, ageing, and CNS injury.